Hepatocellular carcinoma : Treated with hepatic arterial embolization, an analysis of prognostic features in 150 cases - Charindr Eurvilaichit (2018)
From July 1989 to July 1999, 120 male and 30 female patients with hepatocellular carcinoma (HCC), whose ages ranged from 18 to 71 years, were treated by different modalities. The patients were divided into 3 groups according to treatment modalities : group 1 consisted of 35 cases treated by transarterial embolization (TAE) using gelatin sponge permeated with mitomycin-c 20 mg, group 2 - 100 cases treated by transcatheter oily chemoembolization (TOCE) using lipiodol 10 cc with mitomycin-c 20 mg together with gelatin sponge for hepatic embolization, and group 3-15 cases treated by TOCE followed by surgical wedge hepatic resection. The prognostic features following treatments were retrospectively analysed in relation to therapeutic modalities. The results revealed that TOCE was superior to TAE and that TOCE plus adjunct wedge hepatic resection was the best treatment modality with the best cumulative surgical rate (median survival 46.69 months). Analysis of the life-table methods of group 2 patients revealed that the stage of tumors and serum biochemistry on entry, both of which corresponded well with hepatic reserve function were statistically significant prognostic factors for treatment result and long-term outcomes. Further analysis of all the patients also revealed that tumor size and stage of tumors were significant prognostic factors for the treatment of hepatocellular carcinomas.